50 Years of Research on Stunting: A Bibliometric Analysis - Suri, Supian; Sidiq, Fathir Fajar (Department Library of Governance Institut of Home Affairs, 2024)
Background: This study presents a comprehensive review of five decades of research on stunting, an important issue in global public health and nutrition. Using the application of the Scopus database and VOSviewer, a powerful bibliometric analysis tool, this research systematically maps and analyzes the evolution, trends and patterns in the stunting research landscape. Purpose: This study highlights emerging key research themes, influential authors, prolific journals, and collaborative networks. Method: This innovative approach offers valuable insights for researchers, policymakers and practitioners working to combat stunting and its multiple impacts on human development. Result: This innovative approach provides valuable insights for researchers, policymakers and practitioners working to combat stunting and its extensive impacts on human development. Conclusion: This study underscores the importance of continued bibliometric analysis in illuminating the trajectory of scientific inquiry and guiding future research efforts in addressing global health challenges.